Dilemmas and deliberations in managing the care trajectory of elderly patients with complex health needs: a single-case study - Marianne Kumlin; Geir Vegar Berg; Kari Kvigne; Ragnhild Hellesø (BMC, 2022)
Abstract Background Today, the ageing population is larger than ever before, and people who are living longer with chronic illnesses and multimorbidity need support from multiple healthcare service levels. Similarly, healthcare systems are becoming increasingly specialised and fragmented. The World Health Organization has highlighted novel policies for developing integrated and person-centred services. However, patients, next of kin and health professionals face several challenges in managing healthcare during the care trajectory. Limited literature has addressed the challenges experienced by these groups. Therefore, this study aimed to identify the dilemmas and deliberations faced by patients, next of kin and health professionals during the care trajectory of elderly patients with complex healthcare needs. Method The study had a qualitative single-case design. The case was taken from a multi-case study exploring the care trajectory of elderly patients. The participants were the patient, their next of kin and the health professionals involved in the patient's care trajectory. Data were obtained via observation and individual interviews conducted during the patient's hospital stay and after the patient returned home. Results The dilemmas and deliberations in managing the care trajectory were divided into four main themes: the health professionals' pursuit of appropriate and feasible healthcare services, the next of kin's planning horizons, being the person left in limbo and reorganising the home for comprehensive healthcare. Conclusion The pursuit of a tailored and suitable healthcare service lead to a comprehensive mobilisation of and work by all actors involved. Having a comprehensive understanding of these conditions are of importance in developing an appropriate care trajectory for the elderly patient with complex need.